EFEKTIVITAS PELAYANAN SURAT KETERANGAN CATATAN KEPOLISIAN (SKCK) DI POLSEK DRIYOREJO - Astuti, Nani Dwi (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Public service is essentially the provision of excellent service to the community which is the embodiment of the obligations of the government apparatus as a public servant but the condition in the community shows that the public service in the form of police administration service especially in the case of making Police Note Certificate (SKCK) has not fully run well and Encountered obstacles. In this study aims to determine the effectiveness of SKCK service in Driyorejo Polsek where the research is to answer the formulation of the proposed problem. The type of research used in this research is descriptive research with qualitative approach. The survey method used is the interview method to the employees and the community who perform SKCK service. Indicators used are indicators of service effectiveness, which include simplicity, clarity and certainty, security, openness, efficiency, economics, equity and equity and timeliness. Based on the results of interviews obtained can be concluded that the performance of employees who conducted Polsek Driyorejo in serving the community has been effective because the people who do the service already feel good against the performance of officers Driyorejo Police.Keywords : Service Effectiveness, SKCK Service